2009
DOI: 10.1002/ibd.20865
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal carcinoma in indeterminate colitis

Abstract: CRC in IC shares most of the clinical and pathologic features as well as survival outcomes with CRC that occurs in the most prevalent forms of inflammatory bowel disease (IBD), UC and CD. Surveillance regimens currently used in the other forms of IBD seem applicable to IC patients as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A diagnosis of IBDU was considered when the morphology included overlapping features of ulcerative colitis (UC) and Crohn's disease (CD) regarded as inconsistent with either diagnosis (Branco et al, 2009), and all such cases were confirmed after discussions by pathologists, endoscopists, and clinicians. In this series, 261 cases were classified as UC, 189 cases as CD, and 27 cases as IBDU.…”
Section: Methodsmentioning
confidence: 99%
“…A diagnosis of IBDU was considered when the morphology included overlapping features of ulcerative colitis (UC) and Crohn's disease (CD) regarded as inconsistent with either diagnosis (Branco et al, 2009), and all such cases were confirmed after discussions by pathologists, endoscopists, and clinicians. In this series, 261 cases were classified as UC, 189 cases as CD, and 27 cases as IBDU.…”
Section: Methodsmentioning
confidence: 99%
“…It is evident that the variations in the definitions for IBDU can be either too stringent or all encompassing, including as many permutations of the various features that cannot be classified as either UC or CD. [16][17][18] With such a varying background, it is not surprising that the mechanism of this conversion of IBDU to CD remains elusive and difficult to investigate. Finally, our results may reflect that as an IBD surgery team, we may be more aggressive in performing IPAA for IBDU as compared with other institutions especially because we did demonstrate that the long-term outcomes of the ileal pouch were similar in patients with UC or IBDU who underwent IPAA.…”
Section: Discussionmentioning
confidence: 98%
“…Referral center bias must be considered, and also our definition of patients with IBDU may differ from other IBD centers, which had reported different results. 14 We acknowledge the inherent problem of the lack of consensus on the definition of IBDU as a disease entity, [16][17][18][19] but as a tertiary IBD center, we have consistently used the above definition for our practice. In patients with a preoperative diagnosis of IBDU, it would not be unexpected that the rate of developing CD be higher than the estimated 1% to 10% reported in other series of patients that included both UC and IB-DU.…”
Section: Discussionmentioning
confidence: 99%
“…They complaining from overlapping features of inflammatory bowel disease like Ulcerative Colitis (UC) and Crohn's Disease (CD) and confirmed by pathologists, endoscopists, and clinicians as non specific colitis. 10 Colonoscopy, upper gastrointestinal endoscopy, biopsies, serological tests, radiography, and other scanning procedures used for confirming diagnosis. The exclusion criteria were patients with proved UC, CD, malignancy and infectious colitis.…”
Section: Methodsmentioning
confidence: 99%